Teenage Mother's Health across Different Life Stages - Guyonne Kalb; Ha Vu (Institute of Labor Economics (IZA), 2021)
Many women who give birth during their teenage years face lifetime disadvantages in health, social and economic domains. To develop effective policies to support these teenage mothers, it is important to understand how the disadvantage evolves over time to target the timing of any interventions. This paper focuses on health outcomes and seeks to determine the role of teenage motherhood and the likely channels through which teenage motherhood may contribute to health disparities across different life stages between teenage mothers and other women. Using household panel survey data and fixed-effects regressions that control for the effects of prior disadvantage, we show that teenage motherhood is negatively associated with all domains of health and that impacts worsen in later life stages. Potential mediators, including health behaviours, family, social support, education and economic factors are investigated and these partly explain mental health outcomes, reducing the direct impact of teenage motherhood, but not physical health. The strongest pathways are through social support, family and economic outcomes. Our results suggest boosting social support and addressing economic disadvantage may improve mental health outcomes for teenage mothers.
Keywords: I14; I31; J13; 330; teenage motherhood; mental health; physical health; longitudinal analysis